Do female leaders influence bank profitability and bank stability? Evidence from Vietnamese banking sector - Hoang, Hai Yen; Vu, Ngoc; Nguyen, Linh (Economics and Business Letters, 2021)
A diverse board has been seen as an important factor contributing to the success and sustainability of a company. Therefore, policies to enhance the diversity of the boards have been implemented in many countries around the globe. However, previous findings on the impact of female leaders on firm performance still remain inconclusive. Using a dataset of 20 Vietnamese commercial banks over the period from 2013 to 2019, this paper examines whether the gender of the bank leaders such as CEOs or members of Management Team (MT), Board of Directors (BOD) have an impact on bank profitability and bank stability in Vietnam. Our findings suggest that banks with female CEOs tend to be more profitable and more stable than those with male CEOs. However, more women appointed to MT do not necessarily result in more profitable or more stable banks. More interestingly, the presence of women on banks’ board of directors implies lower profitability and more vulnerability for banks. Obtained findings imply important bank governance policies toward better performance and stability for commercial banks in Vietnam. Keywords: gender diversity; bank profitability; bank stability; female leaders JEL Classification Codes: G21, G32, M14, J16, J24